Leading Innovation Towards Universal Prosperity - Omar, Wahid (2015)
Leading innovation would not only strengthen the innovation culture of UTM as an institution, but would also foster and nurture the innovation culture of UTM graduates. We aspire for innovation to be synonymous with UTM and become an ingrained culture.